Aspidistra chongzuoensis (Asparagaceae): a new species from limestone areas in Guangxi, China - Lin, Chun-Rui; Huang, Yu-Song; Zeng, Wei-Bo; Zhu, Fang (Phytotaxa, 2015)
During our fieldwork in the southwest Guangxi, China in January 2014, we found in the White-headed Langur National Nature Reserve an unusual Aspidistra Ker-Gawler (1822: 628) specimen with fruits and dried up flowers only, so we could not identify it without fresh flowers. In November, we returned to the place for further observations of the species, and found the plants with blackish purple, bell-shaped flowers. After consulting herbarium specimens and relevant literature on Aspidistra (Liang & Tamura 2000, Li 2004, Li & Wei 2003, Tillich 2005, 2008, Lin et al. 2009, 2010, 2012, 2013, Lin & Liu 2011, Liu et al. 2011, Tillich & Leong-Skornickova 2013, Hu et al. 2014, Meng et al. 2014, Vislobokov et al. 2014), it became apparent that this population is an undescribed species, and the valid name Aspidistra chongzuoensis was used, which is described below.